Remote digital assessment of amyotrophic lateral sclerosis functional rating scale – a multicenter observational study. Issue 3 (3rd April 2023) - Meyer, Thomas; Spittel, Susanne; Grehl, Torsten; Weyen, Ute; Steinbach, Robert; Kettemann, Dagmar; Petri, Susanne; Weydt, Patrick; Günther, René; Baum, Petra; Schlapakow, Elena; Koch, Jan Christoph; et al.
Abstract: Objective: Remote self-assessment of the revised amyotrophic lateral sclerosis functional rating scale (ALSFRS-R) using digital data capture was investigated for its feasibility as an add-on to ALSFRS-R assessments during multidisciplinary clinic visits. Methods: From August 2017 to December 2021, at 12 ALS centers in Germany, an observational study on remote assessment of the ALSFRS-R was performed. In addition to the assessment of ALSFRS-R during clinic visits, patients were offered a digital self-assessment of the ALSFRS-R – either on a computer or on a mobile application ("ALS-App"). Results: An estimated multicenter cohort of 4, 670 ALS patients received care at participating ALS centers. Of these patients, 971 remotely submitted the ALSFRS-R, representing 21% of the multicenter cohort. Of those who opted for remote assessment, 53.7% ( n = 521) completed a minimum of 4 ALSFRS-R per year with a mean number of 10.9 assessments per year. Different assessment frequencies were found for patients using a computer (7.9 per year, n = 857) and mobile app (14.6 per year, n = 234). Patients doing remote assessments were more likely to be male and less functionally impaired but many patients with severe disability managed to complete it themselves or with a caregiver (35% of remote ALSFRS-R cohort in King's Stage 4). Conclusions: In a dedicated ALS center setting remote digital self-assessment of ALSFRS-R can provide substantial data which is complementary and potentially an alternative to clinic assessments and could be used for research purposes and person-level patient management. Addressing barriers relating to patient uptake and adherence are key to its success.